Performance patterns in Conners' CPT among children with attention deficit hyperactivity disorder and dyslexia - Monica Carolina Miranda; Thais Barbosa; Mauro Muszkat; Camila Cruz Rodrigues; Elaine Girão Sinnes; Luzia Flavia S Coelho; Sueli Rizzuti; Sonia Maria Mota Palma; Orlando Francisco Amodeo Bueno (Arquivos de Neuro-Psiquiatria)
This study investigated the performance of children with attention deficit hyperactivity disorder (ADHD) and dyslexia using Conners' Continuous Performance Test (CCPT). The clinical groups were composed of 52 children with ADHD and 32 children with dyslexia. Performance in the CCPT was evaluated using ANCOVA to compare the clinical groups with the normative Brazilian sample. The ADHD group performed worse than the normative sample in almost all of the measurements, except for reaction time and response style. The dyslexia group scored higher on commissions, variability, perseverations and inconsistency in the reaction time over the six time blocks (Hit SE Block Change) than the children in the normative Brazilian sample. The ADHD and dyslexia groups differed in omission measurements, Hit RT SE, variability, perseverations, Hit RT Interstimulus Intervals (ISI) Change and Hit SE ISI Change. We thus found that the dyslexia group had specific deficit patterns, with greater response to non-target stimuli, greater perseveration and response variability, and difficulties in hit reaction time as the test progressed.